Low vitamin C intake increases risk of pre-eclampsia in high pesticide exposure area - Masrikhiyah, Rifatul; Suhartono, Suhartono; Kartasurya, Martha Irene (Universa Medicina, 2016)
BackgroundPre-eclampsia is the largest direct cause (42%) of maternal mortality death in Brebes district in 2013. The cause of pre-eclampsia is not known with certainty, oxidative stress being one of its causes. The aim of this study was to determine macro- and micronutrient intakes that do not correspond to the needs, as pre-eclampsia risk factors in post-partum women. MethodsThe research was an observational study of case control design. Study subjects were 20-35 year-old post partum women consisting of 55 cases (pre-eclampsia) and 55 controls (non-pre-eclampsia). Nutrient intakes were measured using semi-quantitative food frequency questionnaires and data on levels of pesticide exposure, body mass index (BMI), mid-upper arm circumference (MUAC) and education were collected from structured interviews. Data was analyzed by chi-square tests and multiple logistic regression. ResultsThere was no difference in age and MUAC between the cases and controls. Low vitamin C intake (OR: 20.93; 95% CI: 2.72 – 161.36), high polyunsaturated fatty acid intake (OR: 10.50; 95% CI: 2.47 – 44.57), and low vitamin E intake (OR: 8.57; 95% CI: 2.07 – 35.46) were pre-eclampsia risk factors after controled for pesticide exposure, BMI and education. Low vitamin C intake played the most important role in the incidence of preeclampsia.ConclusionLow vitamin C intake played the most important role toward pre-eclampsia. Greater caution is needed when issuing recommendations regarding the consumption of vitamin supplements in pregnancy, as high doses of some vitamins may be deleterious.